The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1164/rccm.201307-1240oc
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Comorbidities in the Preclinical Stages of Chronic Obstructive Pulmonary Disease

Abstract: Premorbid risk factors and comorbid diseases were more prevalent in the preclinical stages of COPD and smokers without COPD. Physical inactivity and smoking were more strongly associated with the presence of comorbidities compared with airflow obstruction. Clinical trial registered with www.clinicaltrials.gov (NCT 01314807).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 41 publications
(43 reference statements)
6
84
0
5
Order By: Relevance
“…Dyspnea was, in general, present since the initial phases of the disease assisting in the patients searches for diagnosis and presenting direct correlations with the severity of the disease 1,10,28 . Dyspnea caused by pulmonary hyperinflation gets worse during exercise and reduces the patient's capacity to exercise 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyspnea was, in general, present since the initial phases of the disease assisting in the patients searches for diagnosis and presenting direct correlations with the severity of the disease 1,10,28 . Dyspnea caused by pulmonary hyperinflation gets worse during exercise and reduces the patient's capacity to exercise 1 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this reduction in capacity to exercise may be a causal and aggravating factor of the comorbidities in COPD such as skeletal muscular dysfunctions, cardiovascular diseases, obesity and metabolic syndrome 28,29 . The association of self-diagnosed asthma in the group with COPD permits a discussion focused on the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if comorbidities are causally related to COPD and/or share molecular pathways or risk factors (such as ageing, smoking and/or inactivity), the so-called shared component hypothesis [6][7][8][9][10]. Very recently, DIVO et al [11] used network analysis to explore the association between multiple comorbidities in 1969 patients with clinically stable COPD [12].…”
Section: Introductionmentioning
confidence: 99%
“…From these observations, authors suggested (but did not explore) that these comorbidities and clinical characteristics may share pathobiological processes (the shared component hypothesis) [11,12]. Besides, whether or not such potentially shared molecular processes were causally linked to COPD and/or resulted from shared risk factors, such as ageing, smoking and/or inactivity, was also unclear [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…How being physically active affects balance and bone mineral density is inconsistent in the literature [56]. From recent data collected in a population-based cohort of preclinical patients with COPD ((ex-) smokers unaware of their airflow limitation), it was concluded that inactivity and smoking, rather than the disease COPD as such, were the main risk factors for developing comorbid conditions [74].…”
Section: Copd Patientsmentioning
confidence: 99%